Litteratur om och av Elie Wiesel - Illman, Karl-Johan (Nordisk judaistik/Scandinavian Jewish Studies, 1988)
This article reviews some recent books about Elie Wiesel, a three volume edition of his articles and minor writings, and his latest novel.